Risky lifestyles and girls' involvement in crime - Wilcox, Pamela (Gender and crime, 2024)
Building upon the lifestyle-routine activities theoretical tradition (L-RAT), this chapter presents a multilevel conceptual model for understanding the relationship between risky lifestyles and girls’ involvement in crime as either offenders or victims (or both). While the model centers risky lifestyles as a key construct in girls’ involvement in crime, it also draws upon diverse perspectives beyond L-RAT to better understand girls’ risky lifestyles and their effects on girls’ involvement in crime. The model recognizes that risky lifestyles and their effects on girls’ involvement in crime are often intertwined with other microlevel influences, including personal traits, risk preferences, and family circumstances. Further, the model specifies that the effects of risky lifestyles on girls’ involvement in crime are embedded in and potentially conditioned by broader social conditions, including community and macrolevel societal forces. After presentation of the overall model, it further is dissected in an attempt to more closely consider each level through discussion of relevant theory and research.